Magnification endoscopy in combination with acetic acid enhancement and narrow-band imaging for the accurate diagnosis of colonic neoplasms - Shibagaki, Kotaro; Ishimura, Norihisa; Yuki, Takafumi; Taniguchi, Hideaki; Aimi, Masahito; Kobayashi, Keita; Kotani, Satoshi; Yazaki, Tomotaka; Yamashita, Noritsugu; Tamagawa, Yuji; Mishiro, Tsuyoshi; Ishihara, Shunji; Yasuda, Akira; Kinshita, Yoshikazu (Endoscopy International Open, 2020)
Background and study aims Magnification endoscopy with narrow-band imaging (NBIME) and NBIME with acetic acid enhancement (A-NBIME) enable visualization of the vascular and microstructural patterns of colorectal polyp. We compared the diagnostic accuracy and reproducibility of white light endoscopy (WLE), NBIME, and A-NBIME for predictive histologic diagnosis.Patients and methods Consecutive colorectal polyps (N = 628; 38 hyperplasias, 488 adenomas, 72 M-SM1 cancers, and 30 SM2 cancers) were photographed with WLE, NBIME, and A-NBIME. Endoscopic images were independently reviewed by three experts, according to the traditional criteria for WLE, the Japan NBI Expert Team classification for NBIME, and pit pattern classification for A-NBIME to compare diagnostic accuracy and interobserver diagnostic agreement among modalities.Results The specificity (95 % confidence interval) of hyperplasia and SM2 cancer with WLE were 98.2 % (96.8 %–99.1%) and 99.4 % (98.5 %–99.9 %), respectively, showing high accuracy for endoscopic resection without magnifying observation. Diagnostic accuracy of WLE, NBIME, and A-NBIME was 80.8 % (77.4 %–83.8 %), 79.3 % (75.9 %–82.4 %), and 86.1 % (83.2 %–88.7 %), respectively, showing the highest accuracy for A-NBIME among modalities (P < .05). NBIME showed a lower PPV for M-SM1 cancer (P < .05), as with WLE (P = .08) compared to A-NBIME. Fleiss’s kappa values for WLE, NBIME, and A-NBIME diagnosis were 0.43 (0.39 – 0.46), 0.52 (0.49 – 0.56) and 0.65 (0.62 – 0.69), respectively, showing insufficient reproducibility of WLE and superiority of A-NBIME among modalities.Conclusion WLE showed high accuracy for endoscopic resection of colorectal polyps in expert diagnosis. NBIME demonstrated a higher diagnostic reproducibility than WLE. A-NBIME showed possible superiority among modalities in both diagnostic accuracy and reproducibility.